2021
DOI: 10.3892/mmr.2021.12147
|View full text |Cite
|
Sign up to set email alerts
|

LY‑294002 enhances the chemosensitivity of liver cancer to oxaliplatin by blocking the PI3K/AKT/HIF‑1α pathway

Abstract: Liver cancer remains one of the leading causes of cancer deaths worldwide. The therapeutic effect of oxaliplatin on liver cancer is often limited by acquired resistance of the cancer cells. Abnormal activation of the PI3K/AKT pathway plays an important role in the acquired resistance of oxaliplatin. The present study investigated the effects of the PI3K inhibitor LY-294002 and AKT inhibitor MK2206 on the chemosensitivity of oxaliplatin-resistant liver cancer cells and the molecular mechanism involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Liver cancers are characterized by severe intratumoral hypoxia with a median pO 2 of 6 mmHg (0.9% O 2 ) compared with 30 mmHg in normal liver tissue ( 174 ). Phosphatidylinositol-3-kinase and AKT signaling also contribute to increased HIF activity in HCC ( 175 ). Increased HIF-1α expression in the HCC diagnostic biopsy is associated with decreased disease-free and overall survival ( 176 ).…”
Section: Targeting Hifs For Cancer Therapymentioning
confidence: 99%
“…Liver cancers are characterized by severe intratumoral hypoxia with a median pO 2 of 6 mmHg (0.9% O 2 ) compared with 30 mmHg in normal liver tissue ( 174 ). Phosphatidylinositol-3-kinase and AKT signaling also contribute to increased HIF activity in HCC ( 175 ). Increased HIF-1α expression in the HCC diagnostic biopsy is associated with decreased disease-free and overall survival ( 176 ).…”
Section: Targeting Hifs For Cancer Therapymentioning
confidence: 99%
“…Indirubin has also been reported to exert anticancer effects in human cancers (Li Z. et al, 2020). LY-294002 enhances the chemosensitivity of liver cancer to oxaliplatin (Xu et al, 2021). We found here these small-molecule perturbagens might have favorable therapeutic effects for patients in cluster 1, who had the high expression of their target genes.…”
Section: Discussionmentioning
confidence: 53%
“…IGF-1R is a transmembrane tyrosine protein kinase receptor [ 18 , 19 ]. When IGF-1R binds to the corresponding ligand, IGF-1, it catalyzes the phosphorylation of autophosphorylation sites and causes intracellular signal transduction [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tumors in most patients with advanced HCC that are treated with the first-line drug, sorafenib, develop drug resistance [14,15]. Sorafenib-acquired resistance reportedly involves a variety of mechanisms, including multiple-signal pathway crosstalk; abnormal expression of tyrosine kinase receptors, such as PDGFR-β, c-kit, Flt-3, VEGFR and EGFR; epithelial-mesenchymal transition (EMT); and cancer stem-cell differentiation [16][17][18]. In this work, we demonstrated that IGF-1R decreased the sensitivity of HCC to sorafenib treatment; down-regulation of IGF-1R increased the inhibition of sorafenib on the migration of HCC cells mainly through PI3K/Akt and Ras/Raf/ERK pathways.…”
Section: Discussionmentioning
confidence: 99%